2018
DOI: 10.1111/ppl.12793
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term high temperature treatment reduces viability and inhibits respiration and DNA repair enzymes in Araucaria angustifolia cells

Abstract: We evaluated the effect of global warming on Araucaria angustifolia (Bert.) O. Kuntze, a critically endangered native tree of Southern Brazil, by studying the effects of short-term high temperature treatment on cell viability, respiration and DNA repair of embryogenic cells. Compared with control cells grown at 25°C, cell viability was reduced by 40% after incubation at 30 and 37°C for 24 and 6 h, respectively, while 2 h at 40 and 42°C killed 95% of the cells. Cell respiration was unaffected at 30-37°C, but dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In vivo targeting of UNG-GFP fusions and in vitro import assays showed that UNG from Arabidopsis is imported into mitochondria [102]. UNG activity was also found associated to maize and potato mitochondrial fractions [103,104], and in organello experiments revealed UNG in the mitochondria of Arabidopsis, potato, and in the gymnosperm Araucaria angustifolia [102,105].…”
Section: Figure 1 Mechanisms Of Base Excision Repair (Ber)mentioning
confidence: 96%
See 2 more Smart Citations
“…In vivo targeting of UNG-GFP fusions and in vitro import assays showed that UNG from Arabidopsis is imported into mitochondria [102]. UNG activity was also found associated to maize and potato mitochondrial fractions [103,104], and in organello experiments revealed UNG in the mitochondria of Arabidopsis, potato, and in the gymnosperm Araucaria angustifolia [102,105].…”
Section: Figure 1 Mechanisms Of Base Excision Repair (Ber)mentioning
confidence: 96%
“…The Medicago truncatula and Arabidopsis FPG possess a nuclear localization signal [107,110], but the FPG gene can be expressed into seven different mRNAs by alternative splicing [111] and it is possible that some code for organellar isoforms of FPG. The presence of NEI glycosylase activity has recently been characterized in mitochondrial extracts of potato and A. angustifolia [104,105]. Interestingly, Cordoba-Canero et al (2014) found an increase in oxidative damage in both nuclear and mitochondrial DNA from fpg ogg1 Arabidopsis double mutants, but not in single mutants, suggesting that one glycosylase can compensate the absence of the other [106].…”
Section: Figure 1 Mechanisms Of Base Excision Repair (Ber)mentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroplast DNA glycosylase AtNTH1 (endonuclease III homolog 1) has been shown to incise a UV-irradiated supercoiled DNA but not undamaged DNA [123]. Activity of AP endonuclease was confirmed in mitochondria of Arabidopsis, potato and Araucaria angustifolia [115,122,124].…”
Section: Base Excision Repairmentioning
confidence: 99%
“…In addition, in vitro targeting assays have also revealed that a transiently expressed AtUNG-GFP fusion protein in Nicotiana benthamiana leaves is readily colocalized with mitochondria in protoplasts generated from the agro-infiltrated tissues ( Boesch et al, 2009 ). Moreover, some in-organelle experiments have further indicated the presence of UNG activity in the mitochondria in Arabidopsis , potato, and also in the gymnosperm Araucaria angustifolia , respectively ( Boesch et al, 2009 ; Furlanetto et al, 2019 ).…”
Section: Dna Damage Repair Mechanisms In Plant Mitochondria and Chloroplastmentioning
confidence: 99%